2021 7th International Conference on Models and Technologies for Intelligent Transportation Systems (MT-ITS) 2021
DOI: 10.1109/mt-its49943.2021.9529305
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modal management actions for public transport disruptions: an agent-based simulation

Abstract: In a public transport disruption, management of the disruption plays a significant role in reducing passengers' inconvenience. This research aims to evaluate how the delay that passengers experience in a public transport disruption can be reduced, using multi-modal management actions. We consider various traffic management actions implemented in real-time to mitigate the downsides of a disruption, including route and mode adjustments, and capacity increase. Transport operators can implement disruption manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Capacity management can be interpreted as both adding to the capacity of running services, for example, longer buses or trains, or adding to the frequency of running services. Such an analysis has also been investigated for one specific transport line within limited time and locations in Rahimi et al ( 14 ). Their experiment showed that adding to the frequency of service on a line leads to less delay than adding capacity to that service.…”
Section: Disruption Management Actionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Capacity management can be interpreted as both adding to the capacity of running services, for example, longer buses or trains, or adding to the frequency of running services. Such an analysis has also been investigated for one specific transport line within limited time and locations in Rahimi et al ( 14 ). Their experiment showed that adding to the frequency of service on a line leads to less delay than adding capacity to that service.…”
Section: Disruption Management Actionsmentioning
confidence: 99%
“…Previous work also used approaches from the perspective of the network operator and associated cost incurred by them ( 11 , 12 ), based on traffic queue management ( 13 ), information strategies for public transport passengers ( 14 ), real-time information for road disruption ( 15 ), and bus bridging for transport disruption ( 16 , 17 ) to tackle the issue of disruption in road and public transport networks. In summary, the performance of the individual modes (e.g., railway or road traffic) is optimized separately.…”
mentioning
confidence: 99%